3D printed mesh reinforced geopolymer: Notched prism bending. (February 2021) - Santana, Henrique A.; Amorim Júnior, Nilson S.; Ribeiro, Daniel V.; Cilla, Marcelo S.; Dias, Cleber M.R.
Abstract: Geopolymer binders, having high mechanical performance and associated low carbon dioxide (CO2 ) emission, are a promising alternative to Portland cement. However, the brittle fracture of geopolymer matrices may cause catastrophic failure. In this context, seeking to unite the concepts of textile concrete technology and additive manufacturing, this work proposes the development of composites of geopolymer matrices (casted) reinforced with homogeneous or graded PETG meshes (printed). Composites were submitted to the notched prism bending test. The homogeneous reinforcement (volumetric polymer content of 4.75%) and the graded (volumetric polymer content of 3.34%) produced an increase in toughness of 47- and 52-fold, respectively, in addition to conserving the maximum load supported and the critical tension factor of the composites. The gradation of the meshes made it possible to reduce the volumetric content of the reinforcement material without compromising the mechanical performance of the composites. The results show the applicability of 3D printing concepts in the production of printed reinforcements for cementitious matrices. Highlights: 3D printing was used to produce polymeric meshes. The mechanical behavior of a new geopolymer composite was tested. A bending test with notched was applied to evaluate the composites. The gradation in the mesh reduced the consumption of the polymer. The efficiency of the 3D printed polymer mesh was demonstrated.